Myricetin alleviates learning and memory deficits in trimethyltin Alzheimer’s phenotype via attenuating hippocampal endoplasmic reticulum stress and regulating inflammation and oxidative stress - Zahra Asgari; Saeid Iranzadeh; Mehrdad Roghani (Brain Research Bulletin)
Trimethyltin hydrochloride (TMT) induces hippocampal neurodegeneration and learning and memory impairments, providing a useful experimental model for Alzheimer's disease (AD) research. This study aimed to explore the neuroprotective effects of myricetin, a naturally occurring flavonoid with antioxidant and anti-inflammatory properties, against TMT-induced hippocampal damage and elucidate some of its underlying molecular mechanisms. Male NMRI mice (n = 32) were divided into four experimental groups: control, control + myricetin, TMT, and TMT + myricetin. Neurodegeneration was induced by intraperitoneal TMT injection (2.8 mg/kg), followed by daily oral administration of myricetin (25 mg/kg) for 21 days. Learning and memory-related function was assessed using passive avoidance, novel object recognition, and Y-maze tests. After behavioral tasks, hippocampal levels of oxidative stress parameters (glutathione (GSH), superoxide dismutase (SOD), catalase, malondialdehyde (MDA)), inflammatory markers (tumor necrosis factor-alpha (TNF-α), interleukin-10 (IL-10)), and endoplasmic reticulum stress pathway proteins (GRP78, PERK, IRE1α, and CHOP) were evaluated. Histological examinations included Nissl staining to quantify neuronal degeneration in CA1 and dentate gyrus regions, as well as glial fibrillary acidic protein (GFAP) immunohistochemistry. Myricetin treatment attenuated TMT-induced learning and memory impairments and neuronal loss in the CA1 and dentate gyrus subfields. It significantly enhanced hippocampal levels of GSH, SOD and catalase activities, and IL-10 while reducing levels of MDA, TNF-α, and GFAP immunoreactivity. Moreover, myricetin alleviated the TMT-induced elevation of GRP78, PERK, IRE1α, and CHOP. These findings suggest that myricetin holds promise as a therapeutic candidate for AD and other neurodegenerative disorders by counteracting oxidative stress, suppressing neuroinflammation, and modulating endoplasmic reticulum stress pathways.